International consensus guidelines for surgery and the timing of intervention in chronic pancreatitis - Kempeneers, M. A.; Issa, Y.; Ali, U. Ahmed; Baron, R. D.; Besselink, M. G.; Büchler, Markus W.; Erkan, M.; Fernandez-Del Castillo, C.; Isaji, S.; Izbicki, J.; Kleeff, Jörg H.; Laukkarinen, J.; et al. (Pancreatology, 2020)
Background/objectives - Chronic pancreatitis (CP) is a complex inflammatory disease with pain as the predominant symptom. Pain relief can be achieved using invasive interventions such as endoscopy and surgery. This paper is part of the international consensus guidelines on CP and presents the consensus guideline for surgery and timing of intervention in CP. - Methods - An international working group with 15 experts on CP surgery from the major pancreas societies (IAP, APA, JPS, and EPC) evaluated 20 statements generated from evidence on 5 questions deemed to be the most clinically relevant in CP. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach was used to evaluate the level of evidence available for each statement. To determine the level of agreement, the working group voted on the 20 statements for strength of agreement, using a nine-point Likert scale in order to calculate Cronbach’s alpha reliability coefficient. - Results - Strong consensus was obtained for the following statements: Surgery in CP is indicated as treatment of intractable pain and local complications of adjacent organs, and in case of suspicion of malignant (cystic) lesion; Early surgery is favored over surgery in a more advanced stage of disease to achieve optimal long-term pain relief; In patients with an enlarged pancreatic head, a combined drainage and resection procedure, such as the Frey, Beger, and Berne procedure, may be the treatment of choice; Pancreaticoduodenectomy is the most suitable surgical option for patients with groove pancreatitis; The risk of pancreatic carcinoma in patients with CP is too low (2% in 10 year) to recommend active screening or prophylactic surgery; Patients with hereditary CP have such a high risk of pancreatic cancer that prophylactic resection can be considered (lifetime risk of 40-55%). Weak agreement for procedure choice in patients with dilated duct and normal size pancreatic head: both the extended lateral pancreaticojejunostomy and Frey procedure seems to provide equivalent pain control in patients. - Conclusions - This international expert consensus guideline provides evidenced-based statements concerning key aspects in surgery and timing of intervention in CP. It is meant to guide clinical practitioners and surgeons in the treatment of patients with CP.